2006
DOI: 10.1590/s1807-59322006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Perinatal Outcome of 38 Cases With Congenital Diaphragmatic Hernia: 8-Year Experience of a Tertiary Brazilian Center

Abstract: diagnosis and perinatal outcome of 38 cases with congenital diaphragmatic hernia: 8-year experience of a tertiary Brazilian center. Clinics. 2006;61(3):197-202. PURPOSE:To evaluate the perinatal results for neonates with congenital diaphragmatic hernia diagnosed prenatally. METHOD: We reviewed data from 38 cases of congenital diaphragmatic hernia diagnosed prenatally from January 1995 to December 2003 in the Fetal Medicine Unit of the Department of Obstetrics and Gynecology, São Paulo University Medical Schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
(34 reference statements)
2
26
0
6
Order By: Relevance
“…1 ). When it was not possible to identify the ipsilateral lung, we considered the volume almost zero, giving a volume of 0.01 cm 3 , as there was no agenesis of the ipsilateral lung in all cases of CDH studied here.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). When it was not possible to identify the ipsilateral lung, we considered the volume almost zero, giving a volume of 0.01 cm 3 , as there was no agenesis of the ipsilateral lung in all cases of CDH studied here.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers reported, the higher OI predicts a high mortality and has been widely used as criteria for ECMO [27]. Studies using multiple logistic regression analysis identified two adverse prognostic factors: an Apgar score at 1 min (Ap1) of 0-4, and a best oxygenation index (OI) 8.0, low Apgar scores and high oxygenation index (OI) were associated with poor outcome in infants with CDH (higher OI also reflects and triggering the more severe PPHN in comparison to survivors [28].…”
Section: Discussionmentioning
confidence: 99%
“…Other predictors of outcome following FETO are lung size prior to balloon insertion and the ability to remove the balloon prior to birth [34]. Increased survival rates were recently confirmed in a Brazilian randomized trial, though the natural disease of CDH may be different in that setting [35,36]. Therefore, in Europe and Northern America FETO remains an investigational procedure, which now is evaluated in a randomized trial [37,38,39].…”
Section: Introductionmentioning
confidence: 99%